Note on the Regularity of Nonadditive Measures - Toshikazu Watanabe; Syuji Yamada; Tamaki Tanaka (Journal of Applied Mathematics)
We consider the regularity for nonadditive measures. We prove that the non-additive measures which satisfy Egoroff's theorem and have pseudometric generating property possess Radon property (strong regularity) on a complete or a locally compact, separable metric space.